An analysis of secondary stresses in steel parallel chord Pratt trusses - Smith, Megan C. (Kansas State University, 2009)
Trusses have been a common structural system for hundreds of years. The design and analysis of trusses evolved over time to its current state. Most manual truss analyses use the methods of joints and sections under idealized conditions. These ideal conditions, including pinned connections, cause discrepancies between the ideal truss being analyzed and the actual truss being constructed. The discrepancies include joint rigidity, connection eccentricity, and transverse loading. These cause secondary stresses, which induce bending moment into the truss members due to the chord’s continuity. Secondary stresses are most severe in continuous compression chord members. In these members, secondary stresses should be addressed to determine if they are severe and should be included in the truss design, or if idealized analysis will suffice. This report aims to determine the variables that affect the magnitude of secondary stresses in continuous compression chords due to chord continuity. The variables considered are chord stiffness, truss depth, and chord efficiency. Pratt trusses with WT chords were analyzed using the commercial analysis software RISA 3D. Pinned and continuous chord trusses were compared using the interaction value for each chord member. The results were used to determine how these variables affect secondary stresses and how secondary stresses can be predicted. Evaluation criteria were examined to determine the severity of secondary stresses. These criteria examine the radius of gyration, moment of inertia, depth, and section moduli of the chord members, and the moment of inertia of the truss for determination of secondary stress severity. The results of the studies show that secondary stresses increase with increasing member stiffness, decreasing member efficiency, and decreasing truss depth. The necessity for secondary stress consideration can be determined most accurately using the radius of gyration criterion (L/r[subscript]x < 50) for the compression chord.
Keywords: Truss; Secondary stress; Pratt truss; Steel; Engineering, Civil (0543)